Juridical and Philosophical Aspects of Joint Land (Gandhok/Gamblok) Ownership System: Adat Land Law Perspective - Sulastriyono, Sulastriyono (Jurnal Media Hukum, 2019)
Joint land ownership has been in existence for long time in Indonesia, especially in Java. Such a unique ownership system has inherent problem, namely potential conflict among the factual owners. This article aims to analyze the philosophical background of joint land ownership and its legal problems. This normative legal research was conducted through library-based study. It is found that there are three contributing factors that created the joint land ownership system. These include historical factors, philosophical factors, and the change of land economic value. In the past, joint land ownership system was introduced by the head village (bekel) to alleviate the burden of the tax payment. The philosophy of joint land ownership system refers to the philosophy of farmer life that can be identified from several values such as mutual trust and honesty in the spirit of kinship/togetherness.